The body in the gazebo : a Faith Fairchild mystery - Page, Katherine Hall (Page, Katherine Hall. Faith Fairchild mystery., 2011)
When an audit finds money missing from the minister's discretionary fund at Aleford's First Parish Church, suspicion falls on Faith's husband, the Rev. Thomas Fairchild, the only person with access to the account. To complicate matters, Ursula Rowe, Faith's friend Pix Miller's elderly and ailing mother, asks Faith's help in dealing with the disquieting letters she's recently received. Secrets, the kind that fester and can make even strong people ill, reach back to the 1920s.